1991
DOI: 10.1227/00006123-199106000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Transpetrosal-Transtentorial Approach for Sphenopetroclival Meningiomas: Surgical Method and Results in 10 Patients

Abstract: This report presents a new surgical method and the results in 10 patients with petroclival meningiomas extending into the parasellar region (sphenopetroclival meningiomas). Minimal but effective extradural resection of the anterior petrous bone via a middle fossa craniotomy offered a direct view of the clival area with preservation of the temporal bridging veins and cochlear organs. The dural incision was extended anteriorly to Meckel's cave, and in cases with invasion of the cavernous sinus, Parkinson's trian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
216
0
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 429 publications
(227 citation statements)
references
References 0 publications
4
216
0
7
Order By: Relevance
“…The extent of petrosectomy has been widened from the time of introduction of this approach in the neurosurgical field until recently, and this approach is known to be effective for accessing ventral mid-to upper pontine lesions in particular. 1,[4][5][6]9 In fact, when performing the anterior petrosal approach in the narrow space of the parallelogram-shaped anterior surface of the petrous bone, which is bounded by V3, the GSPN, the superior semicircular canal, and the petrous ridge, only approximately 3 cm 2 may not present a straightforward procedure with a manageable learning curve. Adding to the difficulty is the need to preserve the patient's hearing in order to maintain quality of life; a previous comprehensive review reported that 12% of patients who received an anterior petrosectomy due to brainstem cavernous malformations experienced perioperative hear- ing loss.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent of petrosectomy has been widened from the time of introduction of this approach in the neurosurgical field until recently, and this approach is known to be effective for accessing ventral mid-to upper pontine lesions in particular. 1,[4][5][6]9 In fact, when performing the anterior petrosal approach in the narrow space of the parallelogram-shaped anterior surface of the petrous bone, which is bounded by V3, the GSPN, the superior semicircular canal, and the petrous ridge, only approximately 3 cm 2 may not present a straightforward procedure with a manageable learning curve. Adding to the difficulty is the need to preserve the patient's hearing in order to maintain quality of life; a previous comprehensive review reported that 12% of patients who received an anterior petrosectomy due to brainstem cavernous malformations experienced perioperative hear- ing loss.…”
Section: Resultsmentioning
confidence: 99%
“…1 The technique provides easy access to large sphenopetroclival meningiomas, dumbbell-shaped trigeminal schwannomas, and giant acoustic neuromas located in front of the brainstem and basilar trunk aneurysms. 5,7,9 The advantage of this technique is a lower possibility of postoperative hearing loss, vestibulopathy, and facial paresis in comparison with the transcochlear approach and/ or combined middle fossa posterior approach, which both provide similar surgical fields.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neurological examination revealed bilateral papilledema, mildly decreased hearing on the right, hyperreflexia in all 1A). The tumor was subtotally removed via an anterior transpetrosal approach, 6) leaving minimal remnant tumor adherent to the brainstem and perforating arteries. Histological examination confirmed the diagnosis of secretory type meningioma.…”
Section: Case Reportmentioning
confidence: 99%
“…2,4,8,14 Criteria for the selection of these approaches have not been addressed. The goal of this short paper is to clarify the roles of these approaches for the various subtypes of posterior petrous bone meningiomas.…”
mentioning
confidence: 99%